Mixed yeast communities contribute to regionally distinct wine attributes. (1st February 2023) - Hawkins, Diana Lynne; Ryder, Jess; Lee, Soon A; Parish‐Virtue, Katie; Fedrizzi, Bruno; Goddard, Matthew R; Knight, Sarah J
Abstract: There is evidence that vineyard yeast communities are regionally differentiated, but the extent to which this contributes to wine regional distinctiveness is not yet clear. This study represents the first experimental test of the hypothesis that mixed yeast communities—comprising multiple, region-specific, isolates, and species—contribute to regional wine attributes. Yeast isolates were sourced from uninoculated Pinot Noir fermentations from 17 vineyards across Martinborough, Marlborough, and Central Otago in New Zealand. New methodologies for preparing representative, mixed species inoculum from these significantly differentiated regional yeast communities in a controlled, replicable manner were developed and used to inoculate Pinot Noir ferments. A total of 28 yeast-derived aroma compounds were measured in the resulting wines via headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry. Yeast community region of origin had a significant impact on wine aroma, explaining ∼10% of the observed variation, which is in line with previous reports of the effects of region-specific Saccharomyces cerevisiae isolates on Sauvignon Blanc ferments. This study shows that regionally distinct, mixed yeast communities can modulate wine aroma compounds in a regionally distinct manner and are in line with the hypothesis that there is a microbial component to regional distinctiveness, or terroir, for New Zealand Pinot Noir. Abstract : This study shows that mixed yeast communities of vineyards impact wine aroma in a regionally distinct manner in New Zealand Pinot Noir.